Ultrafast spectroscopic investigation of the artificial photosynthetic activity of CuAlS2/ZnS quantum dots. Issue 5 (12th January 2021) - Mukherjee, Arpita; Dutta, Pranab; Bhattacharyya, Biswajit; Rajasekar, Guru Pratheep; Simlandy, Amit Kumar; Pandey, Anshu
Abstract: CuAlS2 /ZnS Quantum dots (QDs) are known to directly convert aqueous solutions of bicarbonate ions to oxygen and organic molecules such as formate with a remarkable efficiency even under sunlight. In cases, fairly complicated organic reaction products such as acetate and methanol have been observed when reactions are allowed to continue for longer periods of time. Here, we investigate the electron dynamics that occurs within CuAlS2 /ZnS QDs and show that it is essentially dominated by ultrafast electron transfer (560 fs for 0.4 excitons per dot) to the surface. The electron dwell time in the conduction band increases exponentially (for example 872 fs for 1.4 excitons per dot) with the excitation fluence. This is reverse of the auger limited response of conventional QDs and is hypothesized to exhibit strong charge separation that lies at the root of the remarkable photocatalytic activity. We further investigate this system through multi‐pump experiments. We find that the system response to prior excitation changes over the period of nanoseconds, consistent with the charge reorganization in the system, well after the initial electron transfer. The results of these experiments are summarized in terms of a coulomb‐well interpretation. Abstract : CuAlS2 /ZnS QDs show remarkable photocatalytic efficiency, readily converting aqueous bicarbonates to organic molecules and oxygen in presence of sunlight. In this article we explore the consequences of ultrafast electron transfer rate (∼560 fs) on their photochemical properties. We find that the electron dwell time increases exponentially with increasing the number of excitons per QD which is reverse compared to the conventional QDs where nonradiative auger recombination leads to rapid multiexciton decay. The charge transfer dynamics is further investigated by two‐pump measurements that show the link between photocatalytic activity and charge reorganization in the system.